2020
DOI: 10.1088/2051-672x/ab9e44
|View full text |Cite
|
Sign up to set email alerts
|

Exploration on tribological behaviour of coumarin as copper rolling oil additive through surface characterization

Abstract: Tribological performance of coumarin in copper rolling oil was studied by four-ball tests and cold rolling tests. Then a systemic investigation on surface topography and surface chemistry of rolled strips was performed by field emission scanning electron microscope (FE-SEM), laser scanning confocal microscopy (LSCM), x-ray diffraction (XRD), x-ray photoelectron spectroscopy (XPS) and Raman spectroscopy (Raman). Results showed that coumarin was a kind of potential lubrication additive. The average friction coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Meanwhile, recent studies have proved that coumarin showed excellent lubrication effects and could be employed successfully in cold-rolling operations. 9,10 Unfortunately, research on corrosion inhibition and surface adsorption mechanism of coumarin, not its derivates, has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, recent studies have proved that coumarin showed excellent lubrication effects and could be employed successfully in cold-rolling operations. 9,10 Unfortunately, research on corrosion inhibition and surface adsorption mechanism of coumarin, not its derivates, has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%